2019
DOI: 10.4995/var.2019.11943
|View full text |Cite
|
Sign up to set email alerts
|

M-BIM: a new tool for the Galleria dell’Accademia di Firenze

Abstract: <p>The paper deals with an ongoing research activity for developing a Building Information Model (BIM) for the facility and collections management of museums. The BIM success lies not only in its application for the design and construction of buildings but also because it helps the information management of a building throughout its life cycle. Compared to other activities, in museums management, the container/content relationship is essential for the preventive conservation of artworks, according to nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The same advantages motivate the growing interest in applying the BIM methodology to various aspects of Cultural Heritage management, both for restoration and museum management (Tucci et al 2019a), or for communication projects also with XR tools (Brioso et al 2019;Pybus et al 2019).…”
Section: State Of the Artmentioning
confidence: 93%
“…The same advantages motivate the growing interest in applying the BIM methodology to various aspects of Cultural Heritage management, both for restoration and museum management (Tucci et al 2019a), or for communication projects also with XR tools (Brioso et al 2019;Pybus et al 2019).…”
Section: State Of the Artmentioning
confidence: 93%
“…The added value of these methods was the integration of survey tools capable of improving the three-dimensional representation of digital models moving from simple points to accurate informative models. Thanks to in-depth analysis and study of application cases that have obtained tangible feedbacks (Brumana et al, 2018;Cabrelles, Blanco-Pons, Carrión-Ruiz, & Lerma, 2018;Tucci et al, 2019), it emerged that the correct creation of complex models mainly depended on four factors:…”
Section: The Era Of Standardization and Bim Interoperabilitymentioning
confidence: 99%
“…Previous research has already shown how the management of museums can benefit from visually structured databases (Tucci et al, 2019a;Tucci et al, 2019b). BIM models (or H-BIM, in the case of museums in historic buildings) including data and 3D representation of works of art help museum managers in decision making by correlating information about the collections and the spaces in which they are located.…”
Section: Virtual Reality For Curatorsmentioning
confidence: 99%